2020
DOI: 10.3390/aerospace7070088
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Morphing Landing Gear Composite Door for High Speed Compound Rotorcraft

Abstract: In the framework of fast rotorcraft, smoothness and flushness of external aerodynamic surfaces present challenges for high-speed conditions, where aerodynamics is the driver of helicopter performance. For AIRBUS-RACER helicopter the main landing gear trap doors are parts of the lower wing skins (in retracted configuration) affecting helicopter performance by minimizing the drag. Flushness requirements must not be in contrast with the functionally of the Landing gear system that must open and close the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Zheng et al [ 205 , 206 ] studied the energy absorption performance of automobile front-end tubes; it was found that when the number of plastic hinges is three, they can absorb energy better and play the role of automobile collision avoidance. Multiple plastic hinges are usually installed in the aircraft cabin to protect the interior safety of the cabin: energy absorbing seats, landing gear and subfloor structures on aircraft are typical applications of plastic hinge deformation and energy absorption [ 207 , 208 , 209 , 210 ].…”
Section: Engineering Applications Of Deformation Instabilitymentioning
confidence: 99%
“…Zheng et al [ 205 , 206 ] studied the energy absorption performance of automobile front-end tubes; it was found that when the number of plastic hinges is three, they can absorb energy better and play the role of automobile collision avoidance. Multiple plastic hinges are usually installed in the aircraft cabin to protect the interior safety of the cabin: energy absorbing seats, landing gear and subfloor structures on aircraft are typical applications of plastic hinge deformation and energy absorption [ 207 , 208 , 209 , 210 ].…”
Section: Engineering Applications Of Deformation Instabilitymentioning
confidence: 99%
“…Further, it is necessary to specify how fine the search must be: If the difference between two consecutive proposals is less than a convergence tolerance, acceptable from a design perspective, the optimizer concludes the job. Before starting the optimization, OptiStruct performs a design sensitivity analysis of the structural responses (with respect to the design variables) to maximize the efficiency of the optimization process [22].…”
Section: Size Optimization With Fem (Second Phase)mentioning
confidence: 99%
“…In particular, among the several subsystems into which aircraft can be divided, landing gears are one of the most complex systems, as they include a wide range of elements, including actuators, shock absorbers, and flexible structures, since they span various physical domains. Recent studies have pushed towards alternative designs [7] and the structural monitoring of nose landing gears [8,9] and their bays [10][11][12], for instance, with strain gauges and fibre Bragg grating techniques. However, the monitoring of the nonstructural aspects of the nose landing gear, for instance, to ensure proper functioning, rather than predicting its residual fatigue life, has not been widely investigated.…”
Section: Introductionmentioning
confidence: 99%